HABITUATION OF RELIGIOUS VALUES AT AN EARLY AGE: STRATEGIES, CHALLENGES AND OPPORTUNITIES - Julfan Hadi; Hendra; Wahyu Mulyadin (Universitas Islam Negeri Mataram, 2025)
This study looks at how Islamic values are taught to young children through daily habits. It focuses on TK Alam J. A Warraihan, an Islamic early childhood school. The research uses a qualitative case study method. Data was collected through observations, interviews, and documents. Teachers, students, and parents were the primary sources of information. The study found that Islamic values are taught through daily routines. These include prayers, polite behavior, and learning in nature. These routines help children grow in mind, heart, and action. Key factors that support this method include teachers being good role models, learning in a natural setting, and parents helping at home. However, there are also challenges. These include limited time, lack of resources, and differences in family backgrounds. This study shows the strengths and weaknesses of using daily habits to teach religion. It adds to ideas about how to build character in Islamic schools. It highlights the value of learning through authentic experiences. The model can be used in other schools to support spiritual and child-centered learning.